Engineering repeat proteins of the immune system. Issue 4 (7th February 2020) - McCord, Jennifer P.; Grove, Tijana Z.
Abstract: Limitations associated with immunoglobulins have motivated the search for novel binding scaffolds. Repeat proteins have emerged as one promising class of scaffolds, but often are limited to binding protein and peptide targets. An exception is the repeat proteins of the immune system, which have in recent years served as an inspiration for binding scaffolds which can bind glycans and other classes of biomolecule. Like other repeat proteins, these proteins can be very stable and have a monomeric mode of binding, with elongated and highly variable binding surfaces. The ability to target glycans and glycoproteins fill an important gap in current tools for research and biomedical applications. Abstract :